How to do everything with Windows Vista Media Center - Ballew, Joli (McGraw-Hill, 2008)
Now you can enjoy all of your digital media on your PC or TV easily with Windows Vista Media Center! Filled with expert tips, this hands-on guide explains how you can watch and record TV shows, download movies and music, view your photos and videos, and so much more--all through one, integrated system. How to Do Everything with Windows Vista Media Center shows you how to configure this versatile tool for optimum quality and performance and how to make the most of all of its powerful--and fun--features